Dampak Boikot Produk Afiliasi Pro Israel Bagi Pertumbuhan Perekonomian di Indonesia - Mairiza, Diany; Hasda, Mifta; Winario, Mohd; Assyifa, Zubaidah; Irmawanti, Irmawanti (EL-EMIR Institute, 2024)
The purpose of this study is to determine the impact of the boycott of pro-Israel affiliated products on economic growth in Indonesia. This research method uses a qualitative approach used to understand the perspectives and attitudes of consumers and industry players towards the boycott of pro-Israel affiliated products. Qualitative data were collected through in-depth interviews and focus group discussions with consumers, traders, and economists. These interviews aimed to explore the reasons behind participation in the boycott, perceptions about the effects of the boycott, and views on local product alternatives. Qualitative data analysis was conducted using thematic coding methods to identify key patterns and themes. The results of this study indicate that the boycott of pro-Israel affiliated products in Indonesia reflects how international political and humanitarian issues can influence economic and social behavior at the national level. While this boycott has the potential to affect the Indonesian economy by reducing demand for imported products and increasing support for local products, the challenges in implementation and its impact on larger political goals remain complex questions. Therefore, there needs to be an in-depth study and a wise approach in dealing with this issue, considering the economic, social, and political impacts holistically.